Trends in Healthcare Costs in Heart Failure and Its Clinical Phenotypes During the Implementation of SGLT2 Inhibitors: A Finnish Registry Study - Hansen, Johan; Tarkia, Miikka; Vasilevska, Marija; Sandin, Patrik; Asllanaj, Eralda; Wammes, Karlijn; Mesterton, Johan; Airaksinen, K. E. Juhani (Dove Medical Press, 2026)
Purpose:
Real-world data on healthcare costs associated with SGLT2 inhibitor use during its early adoption remains limited, particularly across heart failure (HF) phenotypes. This study assessed trends in healthcare resource utilization (HCRU) and costs among HF patients, stratified by SGLT2 inhibitor use and left ventricular ejection fraction (LVEF).
Patients and methods:
Using Finnish specialty care registry data, adults with a first HF diagnosis between January 1, 2016, and June 30, 2022 were identified and categorized by LVEF as reduced (HFrEF), mildly reduced (HFmrEF), and preserved (HFpEF) LVEF. Annual SGLT2 inhibitor uptake (2016– 2022) was assessed. Patients were stratified by SGLT2 inhibitor use within 365 days of HF diagnosis to assess HCRU and costs trends (2016– 2021).
Results:
Among 119,314 patients, 7,626 (6.4%) initiated SGLT2 inhibitors within a year. Among those with LVEF data (n=16,312/119,314 [13.7%]), HFpEF predominated (58%). SGLT2 inhibitor use in HFrEF increased from 14.4% (2020) to 50.1% (2022). Patients receiving SGLT2 inhibitors were younger (70.8 vs 78.6 years), more often male (65.0% vs 47.2%), and had higher prevalence of type 2 diabetes (72.4% vs 28.5%) compared with those without SGLT2 inhibitor use. From 2016 to 2021, inpatient admissions declined modestly across all groups, with consistently shorter stays among patients with SGLT2 inhibitors compared with those not using them (mean: 20.0 vs 26.3 days [2016]; 17.2 vs 21.7 days [2021]). Outpatient visits and drug dispensations were higher in the SGLT2 inhibitor group. Total annual HCRU costs declined over time, remaining lower for SGLT2 inhibitor users (€ 30,742 vs € 34,235 in 2021), driven by reduced inpatient admission costs.
Conclusion:
SGLT2 inhibitor uptake increased notably following regulatory approvals. Patients who received SGLT2 inhibitors had lower healthcare costs driven by reduced hospitalization costs, suggesting economic benefits of early SGLT2 inhibitor initiation in HF management and supporting further research evaluation of long-term cost-effectiveness.